BOOK NOTICES / BOEKAANKONDIGINGS - Lategan, Bernard C. (Scriptura, 1986)
Monsma, Stephen V 1984. Pursuing justice in a sinful world. Grand Rapids: Eerdmans.Curry, Dean C (ed) 1984. Evangelicals and the Bishops’ pastoral letter. Grand Rapids: Eerdmans.Zink, Jörg 1985. Turn toward life: The Bible and peacemaking. Translated from German (Vielleicht ist es noch nicht zu spat) by Victoria Rhodin. Philadelphia: Fortress Press.Simon, Arthur (revised edition) 1984. Bread for the world. Grand Rapids: Eerdmans.Wennberg, Robert N 1985. Life in the balance. Exploring the abortion controversy. Grand Rapids: Eerdmans.Armerding, Carl E 1983. The Old Testament and criticism. Grand Rapids: Eerdmans.Coats, George W 1983. Genesis: with an introduction to narrative literature. Grand Rapids: Eerdmans.Murphy, E Roland. 1983. Wisdom literature: Job, Proverbs, Ruth, Canticles, Ecclesiastes and Esther. Grand Rapids: Eerdmans.Hamlin, E john 1983. Inheriting the land. A commentary on the book of Joshua. Grand Rapids: Eerdmans.Anderson, Robert A 1984. Signs and wonders. A commentary on the book of Daniel. Lux Verbi.Van Selms, A 1985. Job. A practical commentary. Grand Rapids: Eerdmans.Sakenfeld, Katherine D 1985. Faithfulness in action: loyalty in biblical perspective. Fortress Press.Lapide, Pinchas E 1984. Hebrew in the Church. The foundations of Jewish-Christian dialoge. Grand Rapids: Eerdmans.Greenlee, J Harold, 1985. Scribes, scrolls and Scripture. A student’s guide to New Testament textual criticism. Grand Rapids: Eerdmans.Van Hartingsveld, L 1985. Revelation. Text and Interpretation: a practical commentary. Grand Rapids: Eerdmans.Harris, Murray J 1985. Raised immortal. Resurrection immortality in the New Testament. Grand Rapids: Eerdmans.Petersen, Norman R 1985. Rediscovering Paul. Philemon and the sociology of Paul’s narrative word. Philadelphia: Fortress Press.Barrett, C K 1985. Church, ministry, and sacraments in the New Testament. Exeter: The Paternoster Press.Lategan, Bernard C & S Vorster, 1985. Text and reality. Aspects of reference in biblical tests. Philadelphia: Fortress Press.Cranfield, CEB 1985. Romans. A shorter commentary. Grand Rapids: Eerdmans.Lundin, R, Thiselton, A C & Walhout, C 1985. The responsibility of hermeneutics. Grand Rapids: Eerdmans.Guder, Darrell L 1985. Be my witness. Grand Rapids: Eerdmans.Padilla, C René 1985. Mission between the times: Essays on the Kingdom. Grand Rapids: Eerdmans.Shenk, Wilbrt R (ed) 1983. Exploring church growth. Grand Rapids: Eerdmans.Berkhof, Hendrikus 1985. Introduction to the study of dogmatics. Grand Rapids: Eerdmans.Wells, David F (ed) 1985. Reformed theology in America: A history of its modern development. Grand Rapids: Eerdmans.Schwarz, Hans 1985. Divine communication: Word and sacrament in biblical, historical, and contemporary perspective. Philadelphia: Fortress Press.Fackre, Gabriel 1984. The Christian story: A narrative interpretation of basic Christian doctrine. Lux Verbi.Hebblethwaite, Brian 1984. The Christian hope. Grand Rapids: Eerdmans.Gunton, Colin 1985. Enlightenment and alienation: An essay towards a Trinitarian theology. Grand Rapids: Eerdmans.Vos, Arvin 1985. Aquinas, Calvin, and contemporary Protestant thought. A critique of Protestant views on the thought of Thomas Aquinas. Christian University Press.Roth, Robert Paul 1985. The theatre of God. Story in Christian doctrine. Philadelphia: Fortress Press.Mosala, Itumeleng J & Tlhagale, Buti (eds) 1986. The unquestionable right to be frees. Essays in Black Theology. Johannesburg: Skotavlle Publishers.De Gruchy, John 1986. Cry justice!: Prayers, meditations and readings from South Africa. London: Collins.Hick, John 1985. Problems of religious phuralism. Macmillan.Kitawaga, Joseph M (ed) 1985. The history of religions: Retrospect and prospect. Macmillan.Van Leeuwen, Mary Stewart 1985. The person in psychology - a contemporary Christian appraisal. Grand Rapids: Eerdmans.Goldberg, George 1984. Reconsecrating America. Grand Rapids: Eerdmans.Hopfe, Lewis M 1983. Religions of the world. London: Collier Macmillan Publishers.Beversluis, John 1985. C S Lewis and the search of rational religion. Grand Rapids: Eerdmans.